The Huapinghsu Channel/Mienhua Canyon System as a Sediment Conduit Transporting Sediments From Offshore North Taiwan to the Southern Okinawa Trough - Chiang, Cheng-Shing; Yu, Ho-Shing; Noda, Atsushi; TuZino, Taqumi (Frontiers in Earth Science, 2022)
By examining bathymetric and seismic reflection data in the shelf-slope region offshore northeast Taiwan, the morphology of the Huapinghsu Channel/Mienhua Canyon System was refined and occurrence of axial incision in the major erosional trough of the Mienhua Canyon was identified. The Huapinghsu Channel extends from its head at water depth of 120 m seaward across the shelf-slope region and merges with the Mienhua Canyon before finally emptying into the Southern Okinawa Trough. This review with a new idea illustrates this channel/canyon system as a sediment conduit transporting sediments from western Taiwan rivers to the Southern Okinawa Trough. Within the proximal reach of the Mienhua Canyon in-situ suspended particles were found associated bottom nepheloid layers, which transport resuspended particles along the canyon course, and eventually into the Southern Okinawa Trough even during sea-level highstand. The shelf area around the channel head is subject to the influence of frequent occurrences of large typhoons and seasonal migrations of oceanic currents. Numerical examinations indicate that the flow velocities related with large waves or currents satisfy the critical values to threshold of motion of fine sand, implying gravity flows occur around the channel head, sweep unconsolidated sediments in the channel head or even incise the channel floor at the present-day. In this paper, sea level changes from the Last Glacial Maximum (LGM, 18 ka BP) to the present and sediment input to the head of the Huapinghsu Channel head are considered the major factors in the control of the Huapinghsu Channel/Mienhua Canyon system, which functions as a sediment conduit in the study area. Tectonics and climate are the minor factors that contribute to shelf sediment transport to the Southern Okinawa Trough via this channel/canyon system.